Fundamental forces of nature:the story of guage fields - Huang Kerson (World Scientific, 2007)
Gauge fields are the messengers carrying signals between elementary particles, enabling them to interact with each other. Originating at the level of quarks, these basic interactions percolate upwards, through nuclear and atomic physics, through chemical and solid state physics, to make our everyday world go round. This book tells the story of gauge fields, from Maxwell's 1860 theory of electromagnetism to the 1954 theory of Yang and Mills that underlies the Standard Model of elementary particle theory. In the course of the narration, the author introduces people and events in experimental and theoretical physics that contribute to ideas that have shaped our conception of the physical world.
Keywords: Atomic physics; Nuclear physics